Pemikiran Filosof Al-Farrabi dan Ibnu Sina Tentang Filsafat Islam Dan Pendidikan Islam - suardi, alfina; Indo Santalia; salahuddin (Sulesana, 2024)
This The development of Islamic philosophical thought in studying knowledge cannot actually be separated from the contribution of the thoughts of two figures in Islamic philosophy at that time, namely Al-Farabi and Ibn Sina. These two figures also inspired the enlightenment period of European civilization, especially in terms of legal philosophy and science, so that it became a civilization that is quite advanced to this day. This research was conducted to explore the main ideas of the philosophers Al-Farabi and Ibn Sina. The method used in this research is a literature study with primary data from books and journals. The findings in this research are that Al-Farabi's legal philosophy emphasizes the soul as he believes in the existence of a separate rational soul that is capable of achieving happiness through contemplation of intelligible reality. Meanwhile, Ibn Sina's thinking believes that reason can enable progress through various levels of understanding and ultimately lead to God and ultimate truth. In science, Al-Farabi believes that knowledge can be obtained through active reason and intellectual intuition. Meanwhile, Ibn Sina's view of science was very broad and influential, and he believed that knowledge could be obtained through the senses and reason. It is hoped that the implications of this research will be for readers as a motivator in learning the knowledge of Allah, worshiping and practicing to cleanse themselves, guarding every word, deed, heart and mind to always get closer to Allah.